Present Tense : Rock & Roll and Culture - DeCurtis, Anthony (Book collections on Project MUSE., 1992)
The most compelling art form to emerge from the United States in the second half of the twentieth century, rock & roll stands in an edgy relationship with its own mythology, its own musicological history and the broader culture in which it plays a part. In Present Tense, Anthony DeCurtis brings together writers from a wide variety of fields to explore how rock & roll is made, consumed, and experienced in our time. In this collection, Greil Marcus creates a collage of words and pictures that evokes and explores Elvis Presley's grisly fate as an American cultural image, while Rob.